2019
DOI: 10.1002/jso.25617
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative bile spillage is associated with worse survival in gallbladder adenocarcinoma

Abstract: Background: Gallbladder adenocarcinoma is often incidentally identified following cholecystectomy. We hypothesized that intraoperative bile spillage would be a negative prognostic factor.Methods: A retrospective review of patients treated at a cancer center with histologically confirmed gallbladder adenocarcinoma, 2009-2017, was performed.Patient, disease, and treatment factors were analyzed in terms of progression-free survival (PFS) and overall survival (OS).Results: Sixty-six patients were identified. Tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…Although adjuvant therapy is underused in patients with PGC, [31] there is evidence that postoperative adjuvant radiotherapy may be more effective than chemotherapy. [32] Notably, studies have shown that some operation such as routine EBD without bile duct infiltration is not associated with improved overall survival, [33] not to mention that intraoperative bile spillage and surgical drain placement at initial cholecystectomy are negatively associated with overall survival in gallbladder adenocarcinoma, [34] on this aspect systemic therapy are stronger consideration before definitive resection. However, owing to variations in incidence across different countries, it has been understudied, leading to variation in approaches to the initial pathologic evaluation, classification, and staging of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although adjuvant therapy is underused in patients with PGC, [31] there is evidence that postoperative adjuvant radiotherapy may be more effective than chemotherapy. [32] Notably, studies have shown that some operation such as routine EBD without bile duct infiltration is not associated with improved overall survival, [33] not to mention that intraoperative bile spillage and surgical drain placement at initial cholecystectomy are negatively associated with overall survival in gallbladder adenocarcinoma, [34] on this aspect systemic therapy are stronger consideration before definitive resection. However, owing to variations in incidence across different countries, it has been understudied, leading to variation in approaches to the initial pathologic evaluation, classification, and staging of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Factors reported to be prognostic in patients with GBC have included invasion to the bile duct [ 8 ], hepatic invasion [ 9 ], ≥4 regional lymph node metastases [ 10 ], lymph node ratio, total lymph node count [ 11 , 12 ], number of negative lymph nodes [ 13 ], sarcopenia [ 14 ], jaundice [ 15 ], incidental [ 5 ], volume-based PET/CT parameters of total tumor burden of malignancy [ 16 ], intraoperative bile spillage [ 6 ], T stage [ 17 ], stage [ 18 ], and resectability [ 19 ]. However, the circumstances of each research report present difficulties when attempting to generalize the results due to the limitations of each study.…”
Section: Discussionmentioning
confidence: 99%
“…As summarized in Table 2, the univariate and multivariate analyses of the risk factors for overall survival showed that blood loss ≥1400 g (vs. <1400 g, hazard ratio [5]: 2.19), histologically poorly differentiated tumors or others (vs. well-or moderately-differentiated, HR: 2.26), liver invasion ≥5 mm (vs. no invasion, HR: 2.42), ≥4 regional lymph node metastases (vs. no lymph node metastasis [6], HR: 2.25), and treatment without adjuvant chemotherapy (vs. with, HR: 1.93) were independent risk factors. Invasion of the left margin or the entire area of the HDL (vs. no invasion, HR: 1.64, p = 0.053) and postoperative morbidity Clavien-Dindo Classification ≥3 (vs. ≤2, HR: 1.64, p = 0.054) were marginally insignificant.…”
Section: Prognostic Factors In Patients With Stage 3/4 Gbc Without DImentioning
confidence: 99%
“…36 Intraoperative bile spillage could cause cancer cells to spread out of the gallbladder, causing the original disease to progress and upgrade. 37 Third, laparoscopic exploration 38 (one patient in the SAR group) and radical resection 39 (one patient in the SIR group and one patient in the SAR group) were used rarely in this study. The effects of these procedures on long-term prognosis were not analyzed because of the small numbers of patients undergoing these procedures.…”
Section: Discussionmentioning
confidence: 99%